Sistem Informasi Layanan Panti Rehabilitasi Budi Asih Berbasis Web untuk Akses Pendaftaran, Tagihan, dan Ketersediaan Tempat Tidur - Abednego Pebrianto Siregar; Yos Richard Beeh (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2026)
Service information of Budi Asih Rehabilitation Center, such as advanced treatment registration, monthly billing each class and medicine, and remaining beds each class cannot be accessed because it is not yet available online, which requires people to come to the center, which can cause them to go back and forth just to access the information. This study aims to build an information system that can provide the information online for people. This system created using Laravel version 11 and database using MySQL. The research method used in building this information system is Research and Development (R&D). The result is a web application and database that can provide information on online advanced treatment registration, monthly billing information each class and medicine, and remaining beds each class. The tests conducted such as black box testing and User Acceptance Test (UAT) involving 10 respondents. The results showed that the registration time decreased from an average of 20-30 minutes to 5-10 minutes (efficiency above 70%), and information could be accessed in less than one minute. This study only covered the registration, billing, dan bed information features, and did not include patient medical records. The benefit of this system is that detailed dan accurate information about the center can be accessed online by the family of patients anytime and anywhere before deciding to visit the center.